Architecture and Environment for Enabling Interactive Grids - Talwar, Vanish; Basu, Sujoy; Kumar, Raj (Journal of grid computing, 2003)
Traditional use of grid computing allows a user to submit batch jobs in a grid environment. We believe, next generation grids will extend the application domain to include interactive graphical sessions. We term such grids Interactive Grids. In this paper, we describe some of the challenges involved in building Interactive Grids. These include fine grain access control, performance QoS guarantees, dynamic account management, scheduling, and user data management. We present the key architectural concepts in building Interactive Grids viz. hierarchical sessions, hierarchical admission control, hierarchical agents, classes of dynamic accounts, application profiling, user data management, scheduling for interactive sessions, persistent environment settings, and exporting remote desktop. We also describe IGENV, an environment for enabling interactive grids. IGENV consists of GISH –‘Grid Interactive Shell’, Controlled Desktop, SAC –‘Session Admission Control’ module, GMMA –‘Grid Monitoring and Management Agents’, and Policy Engine. We also present our testbed implementation for Interactive Grids using and extending Globus Toolkit 2.0 for the Grid middleware infrastructure, and VNC as the remote display technology.